Wing Morphometric and DNA Barcoding Analysis of Two Different Public Health Important Anopheles Mosquito Species (Journal of the Entomological Research Society, 2021)
Accurate identification and bio-ecology of mosquito vectors is paramount importance in several respects including the development of species-specific vector control strategies. In the current study, we explored two different advance tools such as Geometric morphometric (GM) and DNA barcoding analysis, to supplement morpho-taxonomy based identification of malaria vectors. In landmark-based GM analysis, the pattern of wing shape was examined and we noticed a clear variation in their shape among different Anopheles species. Similarly, in the DNA barcoding studies, the phylogenetic analysis based upon the marker genes such as COI, Cytb and D3 region of 28s rDNA gene sequences were carried out. The neighbour joining tree was formed by distinctive conspecific clusters illustrating genetic variation among different group of Anopheles species. Further, genetic exchange among different Anopheline populations was analysed by considering the COI gene sequences. In the gene flow study, the frequent genetic divergence as well as gene exchange among Anopheles stephensi mosquito populations was observed. Our findings suggested that GM analysis of the wing shape along with DNA barcoding approach can effectively be used together for accurate identification of mosquito vectors including Anopheles stephensi and Anopheles barbirostris.